2018
DOI: 10.1108/imds-09-2017-0427
|View full text |Cite
|
Sign up to set email alerts
|

Risk management and firm performance: the moderating role of supplier integration

Abstract: Purpose The purpose of this paper is to scrutinize the performance effects of supply chain risk management (SCRM). Besides financial performance, two aspects of operational performance are examined: operational efficiency and flexibility. Moreover, the authors explore the moderating role of supplier integration in the relationship between SCRM and operational performance. Design/methodology/approach A survey-based methodology was adopted. Based on the data from an international survey, this study applied the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 73 publications
0
36
0
1
Order By: Relevance
“…For instance, inventory turnover, collaboration with production efficiency, and accuracy of delivery can increase sales and profit [25]. Shou et al [24] also found a moderate positive relationship in inventory turnover between production flexibility and return on sales. Green et al [27] showed that decreasing inventory levels can help firms win more market share and sales volumes.…”
Section: Inventory and Financial Performancementioning
confidence: 99%
See 3 more Smart Citations
“…For instance, inventory turnover, collaboration with production efficiency, and accuracy of delivery can increase sales and profit [25]. Shou et al [24] also found a moderate positive relationship in inventory turnover between production flexibility and return on sales. Green et al [27] showed that decreasing inventory levels can help firms win more market share and sales volumes.…”
Section: Inventory and Financial Performancementioning
confidence: 99%
“…Delivery refers to a performance measure that the ability to deliver products to customers [8]. Flexibility is "a measure of a firm's ability to respond to market demands by switching from one product to another through coordinated policies and actions" [24]. The operational cost, which is always associated with operational efficiency, emphasizes cost savings and increasing profits [8].…”
Section: Theory and Hypothesismentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, our results show no significant relationship between SCRM practices and operational efficiency. This might be ascribed to the fact that SCRM practices require extra investment in buffering strategies such as excess inventories, backup suppliers, preventive maintenance and extra capabilities (Shou et al , 2018a), which further increases manufacturing cost and decreases operational efficiency.…”
Section: Discussionmentioning
confidence: 99%